2010
DOI: 10.3346/jkms.2010.25.3.440
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity Screening in a Multipotent Neural Stem Cell Line Established from the Mouse Brain

Abstract: Neural stem cells (NSCs) have mainly been applied to neurodegeneration in some medically intractable neurologic diseases. In this study, we established a novel NSC line and investigated the cytotoxic responses of NSCs to exogenous neurotoxicants, glutamates and reactive oxygen species (ROS). A multipotent NSC line, B2A1 cells, was established from long-term primary cultures of oligodendrocyte-enriched cells from an adult BALB/c mouse brain. B2A1 cells could be differentiated into neuronal, astrocytic and oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Besides RA, the SH-SY5Y cell line also has been used as a model to study PD when exposed to rotenone, a specific inhibitor of mitochondrial complex I that can cause mitochondria impairment leading to increasing in oxidative stress. The administration of rotenone has been observed to induce cell apoptosis and accumulation of reactive oxidative species (ROS) [49,57,58]. Another study also showed that treatment of SH-SY5Y with rotenone might involve mitochondriaand endoplasmic reticulum-dependent caspase pathways, promoting cell death in concentration-and time-dependent manner [57].…”
Section: Commonly Used Cell Lines For In Vitro Nd Modelmentioning
confidence: 99%
“…Besides RA, the SH-SY5Y cell line also has been used as a model to study PD when exposed to rotenone, a specific inhibitor of mitochondrial complex I that can cause mitochondria impairment leading to increasing in oxidative stress. The administration of rotenone has been observed to induce cell apoptosis and accumulation of reactive oxidative species (ROS) [49,57,58]. Another study also showed that treatment of SH-SY5Y with rotenone might involve mitochondriaand endoplasmic reticulum-dependent caspase pathways, promoting cell death in concentration-and time-dependent manner [57].…”
Section: Commonly Used Cell Lines For In Vitro Nd Modelmentioning
confidence: 99%
“…Characterization of two PSC-derived neuron platforms has demonstrated that derived neurons can be highly sensitive to glutamate and express AMPA and NMDA receptors with physiologically consistent current/voltage relationships and that glutamate-induced excitotoxic cell death (metabolic failure and neurite fragmentation) is mediated through the NMDA receptor in a time-and dose-dependent fashion (Gupta et al 2013;Gut et al 2013). Other stem cell-derived models, including mouse neural stem cells (Choi et al 2010) and hiPSCs (Gupta et al 2013) have also been demonstrated to be suitable for glutamate-induced excitotoxicity research. Other stem cell-derived models, including mouse neural stem cells (Choi et al 2010) and hiPSCs (Gupta et al 2013) have also been demonstrated to be suitable for glutamate-induced excitotoxicity research.…”
Section: Glutamate Toxicitymentioning
confidence: 99%
“…16 Similarly, many efforts have been undertaken to exploit NSCs as a promising tool in neurotoxicity studies, 17 neurodegeneration modeling, drug discovery and gene or cell therapy. 18 So far, studies on the effects of NSCs have not completely elucidated the underlying mechanism with regard to neuronal cultures exposed by toxic agents. In current study to examine whether NSCs-CM could abolish glutamate-induced excitotoxicity or not, glutamate-treated primary cortical neurons were incubated with NSCs-CM and the levels of survival in different concentrations of glutamate-induced excitotoxicity were measured.…”
Section: Introductionmentioning
confidence: 99%